2017
DOI: 10.1111/crj.12614
|View full text |Cite
|
Sign up to set email alerts
|

Differences in inflammatory marker patterns for adult community‐acquired pneumonia patients induced by different pathogens

Abstract: Distinct inflammatory marker patterns were released by different pathogens during acute pneumonia. Significantly increased level of PDGF-BB was observed in acute pneumonia for the first time. It showed a better ability to differentiate MP and virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…We observed E-selectin, MCP-1, ICAM-1, and interferon gamma-induced protein 10 (IP-10) to be most able to differentiate pneumonia from brain injury. These findings matched the elevated concentrations of these mediators previously described in pneumonia 17 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed E-selectin, MCP-1, ICAM-1, and interferon gamma-induced protein 10 (IP-10) to be most able to differentiate pneumonia from brain injury. These findings matched the elevated concentrations of these mediators previously described in pneumonia 17 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Circulating levels of cytokines have been found to be elevated in patients with community acquired pneumonia 13 15 , aid in determining pneumonia severity 16 , and may be able to differentiate causative organisms 17 . However, findings in patients with VAP have been more equivocal 18 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is a known inflammatory cytokine that has an effect on a variety of cells in the immune system, including macrophages 25 . A previous study has shown that along with other inflammatory markers, IL-6 is elevated in patients with bacterial pneumonia 26 . In the murine burn injury – pulmonary infection model, BAL fluid was collected 4 hours after inoculation with PA in sham, untreated PBD1, and MV treated PBD1 mice.…”
Section: Resultsmentioning
confidence: 94%
“…For example, depletion of BPIB3 has been shown to enhance coxsackievirus B (CVB) replication [50]. BPI l levels have also been associated with acute pneumonia in adults [51]. Proteomic analysis showed that several cellular proteins, such as HSP70 and HSP90, were associated with HRSV virus particles, suggesting functional relevance and potential therapeutic targets [52].…”
Section: Discussionmentioning
confidence: 99%